Community participation and sustainable development in the establishment of the |Ai-|Ais/Richtersveld Transfrontier Conservation Park - Myburgh, Kozette (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.